The effect of notch geometry on fracture behavior of glass fiber reinforced polyster - Elaldı, Faruk. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
The aim of this study is to determine quantitatively fracture toughness properties as a function of the crack tip radius, and the effect of fatique damage produced at the crack tip to the critical stress intensity factor, and to examine the fracture behavior of randomly oriented-short-glass. fiber composite. Apart from the intersection of the 5 percent secant line with the load vs displacement curve, two other critical points are observed. These are characterized as the debanding point, and the unstable crack propagation point. Thus, besides evaluating the Kq value using the ASTM standard, two other stress intensity factors are utilized based on the above mentioned critical points. The effect of notch root radius on fracture:properties is observed to be insignificant in the notch root radius range 0.25-2.5 mm for GRP, but not negligible for the polymer matrix. Prior cyclic loading strongly influences the toughness behavior since debonding damage is incurred at the notch root.
Keywords: Glass reinforced plastics.; Fiber reinforced plastics.; Fracture mechanics.